2021
DOI: 10.1039/d1dt02319e
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of silver pentazolates AgN5 and AgN6

Abstract: Silver pentazolate, a high energy density compound containing cyclo-N5- anion, has recently been synthesized at ambient conditions. However, due to high sensitivity to irradiation, its crystal structure has not...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…In the previous studies, Ag-N compounds have attracted widely attention as potential extremely sensitive explosive materials and high energy density materials. In theory, Ag-N polynitrides have been widely studied up to 150 GPa [31,32]. The P2 1 /c-AgN 5 with the structural unit of N 5 ring and P2 1 2 1 2-AgN 6 with the structural units of N 5 ring and N 2 are reported by Williams et al [31].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the previous studies, Ag-N compounds have attracted widely attention as potential extremely sensitive explosive materials and high energy density materials. In theory, Ag-N polynitrides have been widely studied up to 150 GPa [31,32]. The P2 1 /c-AgN 5 with the structural unit of N 5 ring and P2 1 2 1 2-AgN 6 with the structural units of N 5 ring and N 2 are reported by Williams et al [31].…”
Section: Introductionmentioning
confidence: 96%
“…In theory, Ag-N polynitrides have been widely studied up to 150 GPa [31,32]. The P2 1 /c-AgN 5 with the structural unit of N 5 ring and P2 1 2 1 2-AgN 6 with the structural units of N 5 ring and N 2 are reported by Williams et al [31]. In [32], three stable high pressure phases (P4/mmm-AgN 2 , P1-AgN 7 and P-1-AgN 7 ) and two metastable high pressure phases (P-1-AgN 4 and P-1-AgN 8 ) are proposed to enrich the high pressure phase diagram of N-rich Ag-N compounds in the pressure range 0-150 GPa [32].…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] Theoretical works revealed the formation of simple binary pentazolate compounds with much higher content of cyclo-N − 5 by introducing metal elements (e.g., Li, Na, K, Rb, Cs, Be, Mg, Ca, Sr, Ba, Al, Ga, Sc, Y, Cu, Ag, Zn) into the nitrogen system under high-pressure conditions, which indicated that the high-pressure strategy is an alternative route. [1][2][3][12][13][14][15][16][17][18][19][20][21][22][23][24] The synthesis and recovery of simple binary pentazolate compounds are important for their practical applications as HEDMs. Up to now, through high-pressure synthetic techniques, three kinds of simple binary alkali metal pentazolate compounds, such as Li-N 5 , Na-N 5 and Cs-N 5 , have been successfully synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…[ 62 , 63 , 64 ]. Recently, the armchair–antiarmchair N-chain and N 5 ring structures are severally reported for AgN 3 and AgN 5 /AgN 6 compounds [ 65 , 66 ]. Beyond that, no other new silver nitrides with the high-pressure polymeric structures have been reported.…”
Section: Introductionmentioning
confidence: 99%